Review of Appendicitis in Patients With Prolonged Neutropenia. Issue 3 (May 2018) - Atkinson, Brian; Grabau, Michael; Pandya, Shuchi; Aslam, Sadaf; Nanjappa, Sowmya; Dietrick, Clifton; Greene, John N.
Abstract : Abstract: The diagnosis of appendicitis in patients with prolonged neutropenia is difficult. The range of possible infectious agents includes parasites, bacteria, and fungi, all with various presentations. The choice between medical or surgical interventions for the treatment of patients with appendicitis and prolonged neutropenia can be controversial. We report 3 cases of appendicitis in adult patients with prolonged neutropenia and a literature review outlining the effectiveness of medical management versus surgical treatment for appendicitis in prolonged neutropenic populations. Our 3 cases show that there is potential efficacy of medical management in immunocompromised patients with appendicitis. Abstract : The diagnosis and treatment of appendicitis in patients with prolonged neutropenia can be challenging. The choice between medical or surgical interventions for the treatment of prolonged neutropenia patients with appendicitis can be controversial. The authors report three cases of appendicitis that were managed successfully with either medical or surgical interventions.